2003
DOI: 10.1002/bjs.4338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neoadjuvant chemoradiotherapy on angiogenesis in oesophageal cancer

Abstract: Preoperative chemoradiation had little effect on the local angiogenic profile of the tumour in patients with oesophageal cancer. Tumour-infiltrating macrophages seem to be the source of persistent VEGF production after chemoradiotherapy and might explain the raised serum levels. Addition of an antiangiogenic agent to this regimen may be worthwhile in patients with oesophageal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
(34 reference statements)
1
9
0
1
Order By: Relevance
“…In a previous study conducted by McDonnell et al, it was revealed that the mean microvessel density was 6.4 per high-power field in tumors that received preoperative treatment compared with 5.3 per high-power field in those treated by surgery alone. 42 The authors argued that the reactive inflammatory changes occurring in a tumor following chemotherapy may induce an increase in the macrophage population, which in turn results in a persistently high VEGF production, as well as a raised microvessel density. This finding seems to be a reasonable explanation for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study conducted by McDonnell et al, it was revealed that the mean microvessel density was 6.4 per high-power field in tumors that received preoperative treatment compared with 5.3 per high-power field in those treated by surgery alone. 42 The authors argued that the reactive inflammatory changes occurring in a tumor following chemotherapy may induce an increase in the macrophage population, which in turn results in a persistently high VEGF production, as well as a raised microvessel density. This finding seems to be a reasonable explanation for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Great progress has been made in developing therapeutic strategies that target TAMs and VEGF to treat cancer (Kim et al, 1993). Several studies have revealed that TAMs are a very critical cell group in tumor tissue and that TAMs contribute greatly to tumorigenesis and the protection of tumors from therapy (McDonnell et al, 2003). VEGF inhibition represses tumor angiogenesis, and this result has led to the clinical utilization of VEGF inhibitors to treat cancer (Warren et al, 1995;Presta et al, 1997).…”
Section: Microvesicle-delivered Mir-150 Inhibitor Prevents Tumorigenesismentioning
confidence: 99%
“…Tew,Kelsen,Ilson 597 Given that most patients with locally advanced esophageal cancer are treated with concurrent chemoradiation, there may be a possible integrative role for VEGF blockade. Neoadjuvant chemoradiation has a minimal effect on the angiogenic tumor profile (VEGF, von Willebrand factor, CD68, macrophage infiltration), portending a bad prognosis [114]. VEGF blockade reduces tumor interstitial pressure and vascular permeability, thus enhancing radiation and delivery of chemotherapy to tumors [115,116].…”
Section: Vegf Mabsmentioning
confidence: 99%